Four new species of the diving beetle genus Laccophilus Leach, 1815 from Madagascar (Coleoptera, Dytiscidae, Laccophilini) - Manuel, Michaël; Ramahandrison, Andriamirado T. (Zootaxa, 2020)
Four new Laccophilus species are described from Madagascar, three belonging to the L. alluaudi-group (Laccophilus leguyaderi sp. nov., endemic of the Andringitra massif, L. bergsteni sp. nov., endemic of central highland mountains, and L. makay sp. nov., endemic of the Makay massif) and one belonging to the L. laeticulus group (L. rakouthae sp. nov., endemic of the Ankaratra massif). Habitus in dorsal and ventral views and male genitalia are illustrated for the new species (and for comparison, L. alluaudi and L. transversovittatus); furthermore, their habitat preferences and geographical distributions are described and illustrated. An identification key for all species of the L. alluaudi group is provided. The discussion is focused on the interest of the newly described taxa in the context of species radiations in Madagascar.